Quality evaluation of decellularized blood vessels - Bovolato, Ana Lívia de Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Currently, it has been used biological media derived from decellularized tissue and organs in studies, since they have biological advantages. However, it is necessary to make a thorough preparation to ensure the decellularization. Aims: To evaluate the possible existence of DNA in decellularized vessels. Methods: Samples are to infrarenal vena veins of rabbits treated with 1) Sodium deoxycholate (DS) 2% and 2) Sodium dodecyl sulfate (SDS) 1%, with in natura veins as control. After decellularization, the DNA was extracted and quantified by NanoDrop. Thereafter was analyzed on agarose gel. Results: Both evaluated decellularization techniques have DNA remnant. Conclusion: The method of decellularization with SDS shown more efficient that using DS. However, additional studies of optimization and quality control are necessary to ensure the absence of DNA in scaffolds, minimizing problems such as tissue rejection

Não disponivel
Keywords: Vasos sanguineos; Veia cava; Terapia celular; Descelularização; DNA; Medicina regenerativa; Decellularization